Electromechanical energy conversion through active learning - Cardoso, José Roberto 1949-; Salles, Maurício Barbosa de Camargo 1975-; Costa, Mauricio Caldora 1973- (IOP ebooks, 2020)
This book introduces electromechanical energy conversion through active learning. Covering linear and non-linear magnetic circuits, transformers, electromechanical energy and forces, and excited electromechanical systems, along with detailed examination of various machines involved, the book contains numerous 'hands-on' challenges that encourage a creative and determined approach to problem-solving, making it an ideal text for undergraduate courses